Retractive reactions of unstriped muscles of auriferous ways at bronchial asthma in the experiment - L. V. Kapilevich; E. Yu. Dyakova; A. E. Sazonov; E. A. Gereng; A. V. Nosarev (Бюллетень сибирской медицины)
Mechanographical method helped to investigate retractive reactions of unstriped muscle оf auriferous ways at bronchial asthma in the experiment that guinea-pigs had. Sensitization of guinea-pigs by ovalbumin leads to the development of hypersensibility to inhalation of this protein with external characteristics of abnormality of bronchial patency. This process is followed by decomposition of epithelium of bronchi, development of immune inflammation in bronchial wall and hypertrophy of muscle layer. In sensibilized beings there was observed the development of hype reactivity of unstriped muscles of auriferous ways on histamine. It appears in histamine of liminal concentration and increasing of maximal amplitude of contraction. Reactions on choline ergine and β2-adrenergine effect didn't change.